APLIKASI STRUCTURAL EQUATION MODELLING (SEM) PADA KAJIAN PENGARUH KELEMBAGAAN, MODAL SOSIAL JIWA KEWIRAUSAHAAN TERHADAP KINERJA USAHA BUDIDAYA IKAN NILA DI KABUPATEN SLEMAN - Ratna Dewi Mulyaningtiyas (Jurnal Teknosains, 2018)
Social capital becomes the main capital that must be owned by an entrepreneur, thus increasing the entrepreneurial spirit. The purpose of this research is to know the institutional condition of the members of the group of tilapia fish farm, the social capital of the member of the cultivation group of tilapia, the entrepreneurial spirit, farm performance of the tilapia fishery group, and the institutional influence, social capital, entrepreneurial spirit to the business performance of the nila fish farming group in Sleman District. The method used in this research is a method of a mixed method, with 150 responders and analyzed with SEM. The results showed that more than 50% of institutional conditions, social capital, entrepreneurial spirit, and business performance of tilapia fish farming group members of beginners, middle, and main in Ngemplak and Cangkringan Subdistrict Sleman Regency has a high category. There is no significant institutional influence on the influence of social capital on the entrepreneurial. Institutional is not a moderator variable between social capital relations and entrepreneurial spirit. This indicates that the higher/ lower institutional will not result in changes the higher/ lower the influence of social capital on entrepreneurial.